RECONCEPTUALIZING STRATEGIC MARKETING IN THE ERA OF GENERATIVE AI: A DOCTORAL BUSINESS ADMINISTRATION PERSPECTIVE ON VALUE CO-CREATION - Fernando Eko Mardiansyah (Management Studies and Business Journal (PRODUCTIVITY), 2026)
The rapid emergence and adoption of Generative Artificial Intelligence (GenAI) have catalyzed a fundamental paradigm shift in strategic marketing, accelerating the transition beyond mere operational automation toward a sophisticated collaborative intelligence model. This paper explores the profound reconceptualization of modern marketing strategies through the theoretical lens of Service-Dominant Logic (S-DL) and value co-creation. Adopting a Doctor of Business Administration (DBA) perspective, this study investigates how GenAI acts not merely as an efficiency-enhancing tool, but as an active, cognitive participant in the value creation process, bridging the gap between firm-led innovation and customer-driven value. By synthesizing current literature and practical frameworks, this research proposes a new strategic model wherein GenAI facilitates hyper-personalization at scale delivering tailored customer journeys and AI-generated content that adapts to user behavior in real-time. This model redefines the boundaries of marketing, offering a roadmap for balancing technological efficiency with human-centric strategic intent, thereby fostering deeper engagement and sustainable competitive advantage in the digital marketplace.